NMR-based metabolomics for the environmental assessment of Kaohsiung Harbor sediments exemplified by a marine amphipod (Hyalella azteca). Issue 2 (30th November 2017) - Chiu, K.H.; Dong, C.D.; Chen, C.F.; Tsai, M.L.; Ju, Y.R.; Chen, T.M.; Chen, C.W.
Abstract: Inflow of wastewater from upstream causes a large flux of pollutants to enter Kaohsiung Harbor in Taiwan daily. To reveal the ecological risk posed by Kaohsiung Harbor sediments, an ecological metabolomic approach was employed to investigate environmental factors pertinent to the physiological regulation of the marine amphipod Hyalella azteca . The amphipods were exposed to sediments collected from different stream inlets of the Love River (LR), Canon River (CR), Jen-Gen River (JR), and Salt River (SR). Harbor entrance 1 (E1) was selected as a reference site. After 10-day exposure, metabolomic analysis of the Hyalella azteca revealed differences between two groups: E1, LR, CR and JR, SR. The metabolic pathways identified in the two groups of amphipods were significantly different. The results demonstrated that NMR-based metabolomics can be effectively used to characterize metabolic response related to sediment from polluted areas. Highlights: NMR-based metabolomics was applied for risk assessment of sediments. Marine amphipods were exposed to sediments with different pollutant sources. Altered metabolites play as potential biomarkers for environmental pollutants.